A ceria-based solid solution current response catalyst, a preparation method and application thereof
By introducing a second metal into cerium dioxide to form a cerium dioxide-based solid solution current-responsive catalyst, the problem of insufficient redox capacity of cerium dioxide was solved, achieving efficient cracking of light alkanes under mild conditions and improving the selectivity and green preparation of low-carbon olefins.
Patent Information
- Application Number
- CN202411885492.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing petrochemical processes for the preparation of ethylene and propylene are energy-intensive and product distribution is difficult to control. The insufficient redox capacity of cerium dioxide leads to poor catalytic cracking performance.
By introducing a second metal, such as Al, Mn, Fe, Co, Zn, Zr, In, or Sm, into cerium dioxide, a cerium dioxide-based solid solution current-responsive catalyst is formed and prepared by co-precipitation or sol-gel methods, thereby enhancing its conductivity and redox capability.
This method improves the conversion rate of light alkanes and the selectivity of low-carbon olefins under mild conditions, enabling the green preparation of low-carbon olefins, reducing reaction temperature, and suppressing side reactions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of petrochemical technology, and relates to a current-responsive catalyst, its preparation method and application, and particularly to a cerium dioxide-based solid solution current-responsive catalyst, its preparation method and application. Background Technology
[0002] The most mature industrial process for producing ethylene and propylene is naphtha steam cracking, which typically involves a reaction temperature above 800°C. This is a typical high-energy-consuming and high-carbon-emission process, accounting for approximately 40% of the total carbon emissions in the petrochemical industry, and the product distribution is difficult to control.
[0003] "Green electricity" can replace traditional fossil fuels with clean and renewable electricity, providing efficient and controllable energy for petrochemical processes. At the same time, it can regulate the structure and reaction behavior of petroleum molecules and catalytic materials through the action of electric fields, realizing the directional conversion of petroleum molecules into high-value-added chemicals.
[0004] The application of an external electric field powered by "green electricity" holds promise for achieving efficient cracking of light hydrocarbons under mild conditions. The key lies in developing high-performance current-responsive catalysts. Current-responsive catalysts are catalytic materials with suitable conductivity that can generate current under an applied electric field. Molecular sieves are suitable catalysts for catalytic cracking processes; however, molecular sieve materials have poor conductivity. Solid solutions are materials with good conductivity. CN118910661A discloses an integrated solid solution electrode obtained from ruthenium and manganese through a solvothermal reaction; the formation of the ruthenium-manganese solid solution is beneficial to improving the overall stability of the electrode. CN118756095A discloses a Ti2(Al) electrode prepared using high-power pulsed magnetron sputtering technology. 1-x Sn x C solid solution can exist stably in acidic environments and has excellent electrical conductivity.
[0005] This invention improves the conductivity and redox capacity of the resulting material by introducing a second metal into cerium dioxide, thereby solving the problem of poor catalytic cracking performance caused by insufficient redox capacity of cerium dioxide, and realizing the efficient cracking of light alkanes to low-carbon olefins under mild conditions. Summary of the Invention
[0006] The following is an overview of the subject matter described in detail herein, and this overview is not intended to limit the scope of the claims.
[0007] This invention provides a cerium dioxide-based solid solution current-responsive catalyst and its preparation method, which has the advantage of significantly improving the conversion rate of light alkanes and the selectivity of low-carbon olefins under mild conditions, thus realizing the green preparation of low-carbon olefins.
[0008] The technical solution adopted in this application is as follows: The developed cerium dioxide-based solid solution current-responsive catalyst for enhancing the cracking of light alkanes and producing more low-carbon olefins under mild conditions is characterized by Ce. x M 1-x O2 (0 < x < 1) (M is Al, Mn, Fe, Co, Zn, Zr, In or Sm), preparation methods include: co-precipitation method (CP) and sol-gel method (Sol-Gel).
[0009] The co-precipitation (CP) method for preparing cerium dioxide-based solid solution catalysts includes the following steps:
[0010] (1) Add a certain amount of cerium nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0011] (2) Add a certain amount of the second metal precursor to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0012] (3) Pour (2) into (1), stir well, add a certain amount of precipitant, and continue stirring at room temperature. After stirring, let it stand.
[0013] (4) The settled solution was centrifuged, washed, and dried multiple times to obtain a preliminary solid product, which was then calcined to obtain the cerium dioxide-based solid solution catalyst CP-Ce. x M 1-x O2 (0 < x < 1) (M is Al, Mn, Fe, Co, Zn, Zr, In or Sm).
[0014] In step (2) of the above method, the second metal precursor is one of aluminum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, indium nitrate, and samarium nitrate.
[0015] The precipitant in step (3) of the above method is one or more of ammonia, ammonium carbonate or ammonium bicarbonate. After adding the precipitant, the pH of the solution is adjusted to 7-11 and the standing time is 0.5-48h. More preferably, after adding the precipitant, the pH of the solution is adjusted to 8-10 and the standing time is 0.5-36h.
[0016] In step (4) of the above method, the drying temperature is 80-150℃, the drying time is 6-24h, the calcination temperature is 400-700℃, the calcination time is 5-72h, and the heating rate is 2-10℃ / min; more preferably, the drying temperature is 100-120℃, the drying time is 8-12h, the calcination temperature is 500-650℃, the calcination time is 5-48h, and the heating rate is 2-5℃ / min.
[0017] The preparation of cerium dioxide-based solid solution catalysts via the sol-gel method includes the following steps:
[0018] (a) Add a certain amount of cerium nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0019] (b) Add a certain amount of the second metal precursor to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0020] (c) Pour (b) into (a), stir well, add a certain amount of complexing agent, and continue stirring at a certain temperature until the solution becomes a pale yellow gel; and
[0021] (d) The pale yellow gel-like substance was dried to obtain a preliminary solid product, which was then calcined to obtain the cerium dioxide-based solid solution current-responsive catalyst Sol-Gel-Ce. x M 1-x O2 (0 < x < 1) (M is Al, Mn, Fe, Co, Zn, Zr, In or Sm).
[0022] In step (b) of the above method, the second metal precursor is one of aluminum nitrate, manganese nitrate, iron nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, indium nitrate, and samarium nitrate.
[0023] The complexing agent in step (c) of the above method is citric acid, and the molar ratio of the amount of citric acid added to the total metal is (1-3):1, and the stirring temperature is 50-100°C; more preferably, the molar ratio of the amount of citric acid added to the total metal is (1-2.5):1, and the stirring temperature is 60-90°C.
[0024] In step (d) of the above method, the drying temperature is 80-150℃, the drying time is 6-24h, the calcination temperature is 400-700℃, the calcination time is 5-72h, and the heating rate is 2-10℃ / min; more preferably, the drying temperature is 100-120℃, the drying time is 8-12h, the calcination temperature is 500-650℃, the calcination time is 5-48h, and the heating rate is 2-5℃ / min.
[0025] This invention also provides the application of cerium dioxide-based solid solution current-responsive catalysts in the catalytic cracking of light alkanes to produce low-carbon olefins. The application process mainly includes the following steps:
[0026] (i) The prepared cerium dioxide-based solid solution current-responsive catalyst is pressed into tablets, sieved to 20-40 mesh, and 1.85g of the above catalyst is loaded into a fixed-bed reactor equipped with electrodes.
[0027] (ii) In a N2 atmosphere, the reactor is raised to the target temperature, a direct current is applied, and the temperature is stabilized for 2 hours; and
[0028] (iii) Introduce light alkane feedstock to start the reaction, and use gas chromatography to analyze the composition of the product online.
[0029] In the application of the above-mentioned cerium dioxide-based solid solution current-responsive catalyst, the catalytic cracking reaction of light alkanes to produce low-carbon olefins uses C4-C10 alkanes as raw materials and N2 as the carrier gas. The space velocity of the light alkanes is 10-80 mmol / (g·h), the N2 flow rate is 5-60 mL / min, the cracking reaction temperature is 300-450℃, the DC voltage is 0-1000V, the current is 0-3A, and the power is 0-50W. More preferably, the space velocity of the light alkanes is 20-40 mmol / (g·h), the N2 flow rate is 10-50 mL / min, the DC voltage is 0-800V, the current is 0-2A, and the power is 0-30W.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The catalytic material prepared by the cerium dioxide-based catalyst synthesis method provided in this invention incorporates a second metal element M, which can be Al, Mn, Fe, Co, Zn, Zr, In, or Sm, without destroying the cubic fluorite structure of CeO2. This enhances the redox ability of CeO2 and exhibits current response characteristics under a DC electric field; and
[0032] (2) The cerium dioxide-based solid solution current-responsive catalyst provided by the present invention is applied to the reaction of catalytic cracking of light alkanes to produce low-carbon olefins. Under thermoelectric coupling conditions, the reaction temperature is reduced, the catalytic activity is improved, the occurrence of side reactions is suppressed, the selectivity of low-carbon olefins is improved, and the green and low-carbon preparation of low-carbon olefins is realized.
[0033] After reading and understanding the detailed description, other aspects can be understood. Attached Figure Description
[0034] none Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0036] Example 1
[0037] Preparation of cerium-aluminum solid solution current-responsive catalyst CP-Ce by co-precipitation method x Al 1-x O2 (0 < x < 1)
[0038] (1) Add a certain amount of cerium nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0039] (2) Add a certain amount of aluminum nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0040] (3) Pour (2) into (1), stir well, add a certain amount of ammonia water to adjust the pH of the solution to 10, stir continuously at room temperature, and let stand for 24 hours after stirring; and
[0041] (4) The settled solution was centrifuged and washed multiple times, and dried at 110℃ for 10 h to obtain a preliminary solid product. The solid product was calcined at 600℃ for 8 h to obtain the cerium-aluminum solid solution current-responsive catalyst CP-Ce. x Al 1-x O2 (0 < x < 1).
[0042] Example 2
[0043] The cerium-manganese solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Mn 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is manganese nitrate.
[0044] Example 3
[0045] The cerium-iron solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Fe 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is ferric nitrate.
[0046] Example 4
[0047] The cerium-cobalt solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Co 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is cobalt nitrate.
[0048] Example 5
[0049] The cerium-zinc solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Zn 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is zinc nitrate.
[0050] Example 6
[0051] The cerium-zirconium solid solution current-responsive catalyst CP-Ce was prepared using the same method and steps as in Example 1. x Zr 1-xO2 (0 < x < 1), the difference is that the second metal precursor in step (2) is zirconium nitrate.
[0052] Example 7
[0053] The cerium-indium solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x In 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is indium nitrate.
[0054] Example 8
[0055] The cerium-samarium solid solution current-responsive catalyst CP-Ce was prepared according to the same method and steps as in Example 1. x Sm 1-x O2 (0 < x < 1), the difference is that the second metal precursor in step (2) is samarium nitrate.
[0056] Example 9
[0057] Preparation of cerium-aluminum solid solution current-responsive catalysts using the sol-gel method (Sol-Gel-Ce) x Al 1-x O2 (0 < x < 1)
[0058] (a) Add a certain amount of cerium nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0059] (b) Add a certain amount of aluminum nitrate to an appropriate amount of deionized water and stir at room temperature until completely dissolved;
[0060] (c) Pour (b) into (a), stir well, and add a certain amount of citric acid. The molar ratio of citric acid to total metal is 2:1. Stir continuously at 70°C until the solution becomes a pale yellow gel.
[0061] (d) The yellow gel-like substance was dried at 110°C for 10 h to obtain a preliminary solid product. The solid product was then calcined at 600°C for 8 h to obtain the cerium-aluminum solid solution current-responsive catalyst Sol-Gel-Ce. x Al 1-x O2 (0 < x < 1).
[0062] Example 10
[0063] The cerium-manganese solid solution current-responsive catalyst Sol-Gel-Ce was prepared using the same method and steps as in Example 9. x Mn 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is manganese nitrate.
[0064] Example 11
[0065] The cerium-iron solid solution current-responsive catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Fe 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is ferric nitrate.
[0066] Example 12
[0067] The cerium-cobalt solid solution current-responsive catalyst Sol-Gel-Ce was prepared using the same method and steps as in Example 9. x Co 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is cobalt nitrate.
[0068] Example 13
[0069] The cerium-zinc solid solution current-responsive catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Zn 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is zinc nitrate.
[0070] Example 14
[0071] The cerium-zirconium solid solution current-responsive catalyst Sol-Gel-Ce was prepared using the same method and steps as in Example 9. x Zr 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is zirconium nitrate.
[0072] Example 15
[0073] The cerium-indium solid solution current-responsive catalyst Sol-Gel-Ce was prepared using the same method and steps as in Example 9. x In 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is indium nitrate.
[0074] Example 16
[0075] The cerium-samarium solid solution current-responsive catalyst Sol-Gel-Ce was prepared according to the same method and steps as in Example 9. x Sm 1-x O2 (0 < x < 1), the difference being that the second metal precursor in step (b) is samarium nitrate.
[0076] Application examples
[0077] The series of cerium dioxide-based solid solution current-responsive catalysts obtained in Examples 1-16 were used to catalyze the cracking of light alkanes. The evaluation device used was a microelectrode fixed-bed reactor, and the specific process is as follows:
[0078] (i) The prepared cerium dioxide-based solid solution current-responsive catalyst powder is pressed into tablets, sieved to 20-40 mesh, and 1.85g of the above catalyst is loaded into a microelectrode fixed bed reactor.
[0079] (ii) Controlling the N2 carrier gas flow rate to 40.0 mL / min, the reactor was heated to the set temperature in the N2 atmosphere, and a direct current (0 / 8 W, where 0 W represents no electric field and 8 W represents the power under an applied electric field) was applied, and the temperature was stabilized for 2 hours; and
[0080] (iii) The reaction was started by introducing light alkane feedstock, with a light alkane space velocity of 40 mmol / (g·h). The composition of the product was analyzed online by gas chromatography, with samples taken every 1 h. The results in the table are the average data over a reaction period of 3 to 5 h.
[0081] The conversion rates and selectivity of the main products are shown in Tables 1 and 2. (In the tables, "trienes" includes ethylene, propylene, and butene; "BTX" includes benzene, toluene, and xylene.)
[0082] Table 1. Performance of the cerium dioxide-based solid solution current-responsive catalysts prepared in the examples in cracking n-hexane under conditions with and without electric field.
[0083]
[0084] Note: 0W represents no electric field, and 8W represents the power under an applied electric field.
[0085] Table 2. Performance of the cerium dioxide-based solid solution current-responsive catalysts prepared in the examples on and off electric fields for cleaving n-octane.
[0086]
[0087] Note: 0W represents no electric field, and 8W represents the power under an applied electric field.
Claims
1. A method for enhancing the cracking of light alkanes to produce more low-carbon olefins and byproducts of benzene, toluene, and xylene under an electric field using a cerium dioxide-based solid solution current-responsive catalyst, wherein the low-carbon olefins include ethylene, propylene, and butene; the current-responsive catalyst is characterized by a Ce2O3 composition. x M 1-x O2, 0 < x < 1, M includes Al, Mn, Fe, Co, Zn, Zr, In or Sm.
2. According to the method of claim 1, direct current is used in the catalytic cracking of light alkane, with a voltage of 0.1-1000V, a current of 0.01-3A, and a power of 0.001-50W.
3. The method according to claim 1, wherein the catalytic cracking temperature of the light alkane is 300-450℃.
4. The method according to claim 1, wherein the light alkane is an alkane with a chain length of C4-C10.
Citation Information
Patent Citations
Conductive corrosion-resistant solid solution MAX phase composite coating as well as preparation method and application thereof
CN118756095A
Cerium-based solid solution and preparation method and application thereof
CN111569892A